UNRAVELING COMPLEXITY: THE ROLE OF MORPHOLOGICAL STRUCTURE IN READABILITY AND COMPREHENSION CHALLENGES OF AGGLUTINATIVE LANGUAGES: https://doi.org/10.5281/zenodo.20823463 - Jo‘rayev , Muhammadrahimxon (Scientific practical conference, 2026)
Agglutinative languages, by their morphological properties, form words by a systematic use of affixes to a root. Therefore, many complex words can be formed by prefixes and/or by suffixes and/or by an infix, and in these languages each affix has one fixed grammatical function.